2012
DOI: 10.1093/humrep/des346
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ CD25+ FOXP3+ regulatory T cells in peripheral blood and peritoneal fluid of patients with endometriosis

Abstract: This study was supported by 1M15/N/2011 and NK1W grants from the I Faculty of Medicine, Warsaw Medical University. None of the authors has any competing interests to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(71 citation statements)
references
References 31 publications
5
60
0
1
Order By: Relevance
“…Disturbance of T reg cells, which are responsible for self-tolerance, maintenance of immune homeostasis, and immunosuppressive functions, 22 aggravates the condition of endometriosis. In this study, we have demonstrated not only that the percentage of T reg cells in the peritoneal fluid of endometriosis patients higher than that in healthy women, which is consistent with results of previous published studies, 23 but also that the augmentation of T reg cell percentage, especially that of TGF- β 1 + T reg cells, occurs in parallel with endometriosis exacerbation. This suggests that the detection of peritoneal T reg cells may be used as an indicator to assess the severity of endometriosis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Disturbance of T reg cells, which are responsible for self-tolerance, maintenance of immune homeostasis, and immunosuppressive functions, 22 aggravates the condition of endometriosis. In this study, we have demonstrated not only that the percentage of T reg cells in the peritoneal fluid of endometriosis patients higher than that in healthy women, which is consistent with results of previous published studies, 23 but also that the augmentation of T reg cell percentage, especially that of TGF- β 1 + T reg cells, occurs in parallel with endometriosis exacerbation. This suggests that the detection of peritoneal T reg cells may be used as an indicator to assess the severity of endometriosis.…”
Section: Discussionsupporting
confidence: 92%
“…One is homing of peripheral T reg cells to the peritoneal fluid as the percentage of T reg cells decreases in the peripheral blood of EMS patients. 23 The second is that local naive T cells differentiate into T reg cells under the influence of various factors involved; and the third is self-proliferation of local T reg cells. In fact, all of these assumptions may be involved in the increase of peritoneal T reg cell percentage in endometriosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treg is another subset of helper T cells and they are known to maintain immunological tolerance. 66 Many studies have shown that Treg are increased in the peritoneal cavity of endometriosis patients [84][85][86][87] ; however, two studies did not find a significant difference. 73,88 In a mouse study, the inhibition of Treg induction (differentiation) reduced the number and weight of endometriotic lesions.…”
Section: Th17 and Treg In Endometriosismentioning
confidence: 98%
“…One study found increased Treg cells in the peritoneal fl uid and decreased levels in the peripheral blood of women with endometriosis compared to controls without endometriosis. The authors suggest a possible shift from the peripheral blood to the affected tissue as a compensatory method to modulate infl ammation [ 85 ]. Treg cell abnormalities, such as polymorphisms of FOXP3 gene and increased levels of transcriptional factors for FOXP3, have been found in endometriotic lesions [ 86 , 87 ].…”
Section: Immunologymentioning
confidence: 99%